2023
DOI: 10.3389/fgene.2023.1004481
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting artificial intelligence diagnosis of hepatocellular carcinoma with DIKWH framework

Abstract: Hepatocellular carcinoma (HCC) is the most common type of liver cancer with a high morbidity and fatality rate. Traditional diagnostic methods for HCC are primarily based on clinical presentation, imaging features, and histopathology. With the rapid development of artificial intelligence (AI), which is increasingly used in the diagnosis, treatment, and prognosis prediction of HCC, an automated approach to HCC status classification is promising. AI integrates labeled clinical data, trains on new data of the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…The detection rate of liver CEUS in detecting early hepatocellular carcinoma has been questioned, and it is still necessary to combine computed tomography (CT), magnetic resonance imaging (MRI), and some biomarkers to improve the detection rate ( 12 ). However, some researchers have found that MRI has higher resolution and contrast enhancement function compared to ultrasound and CT, and it is recommended to be the preferred imaging method for hepatocellular carcinoma diagnosis ( 13 ). Therefore, in order to verify the application value of CEUS in early hepatocellular carcinoma diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The detection rate of liver CEUS in detecting early hepatocellular carcinoma has been questioned, and it is still necessary to combine computed tomography (CT), magnetic resonance imaging (MRI), and some biomarkers to improve the detection rate ( 12 ). However, some researchers have found that MRI has higher resolution and contrast enhancement function compared to ultrasound and CT, and it is recommended to be the preferred imaging method for hepatocellular carcinoma diagnosis ( 13 ). Therefore, in order to verify the application value of CEUS in early hepatocellular carcinoma diagnosis.…”
Section: Introductionmentioning
confidence: 99%